The Influence of Tourism Activities, Local Spending, and Macroeconomic Indicators on Provincial Economic Growth in Indonesia - Hidayati Fatahillah; Ghozali Maski; Rachmad Kresna Sakti (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
This study is driven by the critical role of the tourism sector, local fiscal policies, and macroeconomic indicators in stimulating local economic growth in Indonesia, which continues to exhibit significant disparities across provinces. The purpose of this study is to analyze the influence of the number of domestic and international tourists, tourist spending, occupancy rates of starred and non-starred hotels, local government spending, inflation, exchange rates, and infrastructure on provincial economic growth in Indonesia for the period 2018–2023. The method used is a quantitative approach with an explanatory design using panel data from 11 provinces, which were analyzed using a Random Effects Model. The results show that only foreign tourist spending, occupancy rates of starred hotels, inflation, exchange rate, and infrastructure have a significant influence on economic growth, while other variables are insignificant. This finding indicates that tourism quality, macroeconomic stability, and infrastructure support are more determinant than tourist quantity or local government spending. The implications of this study emphasize the importance of policies that focus on increasing high-value tourism, public spending efficiency, and strengthening infrastructure and economic stability. In conclusion, local economic growth in Indonesia is more influenced by the quality and efficiency of the economy than simply increasing the volume of tourism activity.